2013
DOI: 10.1186/1471-2148-13-188
|View full text |Cite
|
Sign up to set email alerts
|

Delayed colonisation of Acacia by thrips and the timing of host-conservatism and behavioural specialisation

Abstract: BackgroundRepeated colonisation of novel host-plants is believed to be an essential component of the evolutionary success of phytophagous insects. The relative timing between the origin of an insect lineage and the plant clade they eat or reproduce on is important for understanding how host-range expansion can lead to resource specialisation and speciation. Path and stepping-stone sampling are used in a Bayesian approach to test divergence timing between the origin of Acacia and colonisation by thrips. The evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 104 publications
1
6
0
Order By: Relevance
“…Multiple phylogenetic studies that incorporated molecular clock analyses have shown that contemporaneous parallel cladogenesis has not been common in the evolution of plants and their herbivorous insects [ 10 15 ]. Also little evidence has been found for ‘asynchronous parallel cladogenesis’, where plants diversified first and herbivores later mirrored the speciation events of their hosts through resource tracking [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple phylogenetic studies that incorporated molecular clock analyses have shown that contemporaneous parallel cladogenesis has not been common in the evolution of plants and their herbivorous insects [ 10 15 ]. Also little evidence has been found for ‘asynchronous parallel cladogenesis’, where plants diversified first and herbivores later mirrored the speciation events of their hosts through resource tracking [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to test for successive burst of diversification in plants and insects, many authors have thus simply compared the timing of divergence of plants and associated insects (e. g., Brandle et al 2005;Gómez-Zurita et al 2007;Kergoat et al 2011;Kergoat et al 2015;Leppanen et al 2012;Lopez-Vaamonde et al 2006;McKenna et al 2009;McLeish et al 2013;Pena & Wahlberg 2008;Segar et al 2012;Stone et al 2009;Vea & Grimaldi 2016;Wahlberg et al 2013). Most of these studies suggest delayed colonization of already diversified groups of plants by insects groups at different temporal scales.…”
Section: Ii1) Comparing the Phylogenies Of Plants And Insectsmentioning
confidence: 99%
“…In order to test for successive burst of diversification in plants and insects, many authors have thus simply compared the timing of divergence of plants and associated insects (e. g., Brandle et al 2005;Gómez-Zurita et al 2007;Kergoat et al 2011;Kergoat et al 2015;Leppanen et al 2012;Lopez-Vaamonde et al 2006;McKenna et al 2009;McLeish et al 2013;Pena & Wahlberg 2008;Segar et al 2012;Stone et al 2009;Vea & Grimaldi 2016;Wahlberg et al 2013;Winter et al 2017). Most of these studies suggest delayed colonization of already diversified groups of plants by insects groups at different temporal scales.…”
Section: Phylogenetic Approaches For Testing Ecological Speciation Sc...mentioning
confidence: 99%